Strategi Layanan Keamanan Siber pada Ekosistem Multi-Platform: Tinjauan Literatur - Khairudiah Khairudiah; Reifan Reifan; Alam Al Hasbi; Nasywa Az zahra; Farid Deza Amin (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid escalation of digital technology adoption has compelled modern organizations to operate within complex multi-platform ecosystems, integrating diverse operating systems, mobile devices, web applications, and cloud services. While this convergence enhances operational agility, it significantly expands the potential attack surface, exposing critical assets to sophisticated cyber threats. This study employs a Systematic Literature Review (SLR) methodology to evaluate and compare contemporary cybersecurity strategies. Analyzing 15 primary studies selected from reputable databases between 2018 and 2024, this research contrasts the efficacy of Perimeter-based models, Defense-in-Depth, and Zero Trust Architecture (ZTA). The findings demonstrate that traditional static security perimeters are obsolete in decentralized environments. Conversely, a hybrid approach combining Zero Trust with AI-driven threat detection offers superior resilience, reducing incident response latency and preventing lateral movement. The study concludes by proposing an integrated security framework that positions cybersecurity as a strategic business enabler rather than a technical support function.